EFEKTIVITAS STRATEGI PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN MOTIVASI BELAJAR - Sri Bangun; Abdul Rachman Syam Tuasikal; Mochamad Ridwan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effectiveness of differentiated learning strategies in improving students’ learning motivation in Physical Education (PJOK) classes. The research was conducted in response to low student motivation, which was reflected in limited engagement, low enthusiasm, and insufficient persistence during learning activities. This study employed a pre-experimental design with a one-group pretest–posttest model involving 35 eleventh-grade students of SMK Negeri 1 Jenangan Ponorogo. A motivation questionnaire measuring interest, enthusiasm, persistence, and active engagement was used as the research instrument. Data were analyzed using the paired sample t-test after confirming normal distribution. The results showed an increase in the average motivation score from 48.06 (71.75%) in the pretest to 56.91 (75.88%) in the posttest. The paired sample t-test revealed a significance value of 0.001 < 0.05, indicating a statistically significant difference between pretest and posttest motivation scores. These findings demonstrate that differentiated learning strategies are effective in enhancing students’ learning motivation in PJOK lessons.